2011
DOI: 10.1002/bjs.7766
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting outcome after traumatic limb amputation

Abstract: Background: Traumatic leg amputation commonly affects young, active people and leads to poor longterm outcomes. The aim of this review was to describe common causes of disability and highlight therapeutic interventions that may optimize outcome after traumatic leg amputation.Methods: A comprehensive search of MEDLINE, Embase and Cumulative Index to Nursing and Allied Health Literature databases was performed, using the terms 'leg injury', 'amputation' and 'outcome'. Articles reporting outcomes following trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 129 publications
2
53
0
3
Order By: Relevance
“…Perkin's review found a significant increase in anxiety and depression compared to the population average with femoral amputation but not with tibial amputation [13]. This suggests that the higher the severity of the injury, the more likely the patient will be to suffer from a mental illness.…”
Section: Discussionmentioning
confidence: 97%
“…Perkin's review found a significant increase in anxiety and depression compared to the population average with femoral amputation but not with tibial amputation [13]. This suggests that the higher the severity of the injury, the more likely the patient will be to suffer from a mental illness.…”
Section: Discussionmentioning
confidence: 97%
“…Perkins et al [7] observed an increase in blood pressure at rest in patients with traumatic amputations compared with nonamputated individuals. In addition, only 1.8% of these patients presented low blood pressure levels.…”
Section: Introductionmentioning
confidence: 97%
“…The increased morbidity and mortality in amputees can be explained by the development of risk factors, among which high blood pressure plays an important role [6][7][8][9]. Perkins et al [7] observed an increase in blood pressure at rest in patients with traumatic amputations compared with nonamputated individuals.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of the need for reconstruction in the lower limb after major trauma is by itself a poor prognostic factor for expecting the improvement in the functional index [15]. Amputation is suggested as the best alternative in many studies [7,8] but is called into question by many others [16][17][18].…”
Section: Discussionmentioning
confidence: 99%